KETUNTASAN BELAJAR SISWA PADA MATA DIKLAT KEWIRAUSAHAAN DENGAN PENERAPAN MEDIA PEMBELAJARAN BLOG (E-LEARNING) - Begron Gegap. S, (Pendidikan Ekonomi, 2011)
The research was conducted to investigate the use of blog (e-learning) to achieve the learning mastery of the students in entrepreneurship course. Specifically, it was intended to find out the teachers and students activities in learning process, the students learning result, and response to the use of blog. The study was classroom action research. The results revealed that the students and teachers activities improved in the second cycle. The percentage of students who achieved the learning mastery in the first cycle was 79.48 %. In the second cycle, it increased by 89.74 %. The students had positive response to the use of blog (e-learning) as a learning medium.